PERAN KECINTAAN MEREK DALAM MEMBANGUN HUBUNGAN DENGAN PELANGGAN (Studi pada Pengguna iPhone di Denpasar) - Wirawan, I Dewa Gede Kresna; Sukaatmadja, I Putu Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.06.TAHUN 2018DO - 10.24843/EEB.2018.v07.i06.p09, 2018)
The purpose of this study is to examine the role of brand love with a causal approach and factors that build consumer brand relationships (brand identification, brand trust and brand commitment) that impact on word-of-mouth and willingness to pay premium prices on iPhone users. Testing hypothesis research using Partial Least Square method with a sample of 100 people who are domiciled in Denpasar. Determination of sample with nonprobability sampling method, that is purposive sampling, with respondent criterion that use smartphone iPhone for last 2 years. The findings in this study indicate that brand identification has a positive and significant impact on brand love and brand commitment. Brand trust has a positive and significant impact on brand love and brand commitment. Brand love has a positive and significant impact on brand commitment, word-of-mouth, and willingness to pay at a premium price. Brand commitment has a positive and significant effect on word-of-mouth and on willingness to pay at a premium price. This study has implications that it is important for management to increase brand awareness of the iPhone so that users can easily recognize the brand through product form, product durability, and sophistication. This will impact on a positive assessment of the iPhone and increase the user's emotional so users see the iPhone is the best brand.